Prevalência de sífilis, conhecimentos e fatores comportamentais em jovens do Exército Brasileiro, Brasil 2007 - Ribeiro, Denis (2010)
The objectives of this study were to describe the prevalence of syphilis (positivity in the treponemal test) by geographic region and frequency of behaviors and symptoms related to STD and describe knowledge of military draftees related to STD. A cross-sectional study was performed with the draftees who attended the Brazilian Armed Forces in 2007. The young males answered a self-administered questionnaire on sociodemographic issues, sexual practice and condom use, occurrence of signs and symptoms of STD and had a blood sample collected for the treponemal test for syphilis. A total of 35,460 draftees answered the questionnaire and 75.5% of these had already had sexual intercourse. The overall prevalence of syphilis was 0.53% (95% CI 0.45%-0.61%) and by geographic region: North (0.85%), Northeast (0.82%), and nearly double the 11 Midwest region (0.49%) and more than double the Southeast (0.34%) and South (0.26%). Having 17 years old [OR = 1.3 (95% CI 1.05-1.73)], having completed primary education [OR = 1.5 (95% CI 1.03-2.22)], living in the north/northeast region of the country [OR = 1.2 (95% CI 1.04-1.36)], reporting a history of STD [OR = 2.7 (95% CI 1.03-6.99)], being MSM [OR = 4.5 (95% CI 2.59-7.81)], and reporting genital ulcer disease [OR = 2.6 (95% CI 1.59-4.26)] were associated with syphilis. Variables associated with lower education (up to eight years of education) were: being 19-20 years old [OR 1.2 (95% CI: 1.18 to 1.32)], STD transmission by eating contaminated food [OR 2.2 (95% CI: 1,96-2.55)], by bathing in rivers/beaches [OR 1.5 (95% CI: 1.27-1.88)], by mosquito bites [OR 1.5 (95% CI: 1.38-1.65)], and by having sexual intercourse <=14 years old [OR 1.4 (95% CI: 1.33-1.55)]. Variables were negatively associated: being white [OR 0.9 (95% CI: 0.82-0.91)], knowing that the infection was due to the sharing of syringes and needles [OR 0.7 (95% CI: 0.62-0.78)], mother-to-child transmission [OR 0.6 (95% CI: 0.58-0.69)], having used a condom in the last sexual intercourse [OR 0.8 (95% CI: 0.71-0.85)], MSM [OR 0.7 (95% CI: 0.60-0.92)], and knowing that having sex without condoms increases the risk of transmission [OR 0.4 (95% CI: 0,37-0,51)]. STD education programs must be dynamic and comprehensive; involving teens, their parents and educators, for isolated knowledge about ways STD transmission is not sufficient for full protection of young people.